The philosophy shop ideas, activities and questions to get people, young and old, thinking philosophically - Worley, Peter; Worley, Peter; Adamson, Harry; Adamson, Peter; Archer, Alfred; Ayala, Saray; Bartley, Grant; Birch, David; Cave, Peter; Christofidis, Miriam Cohen; Cowell, Philip; Davy, James; et al. (Independent Thinking Press, 2012)
A veritable emporium of philosophical puzzles and challenges to develop thinking in all classrooms.